2019
DOI: 10.1002/bjs.11286
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre analysis of the learning curve for laparoscopic liver resection of the posterosuperior segments

Abstract: Background: Laparoscopic liver resection demands expertise and a long learning curve. Resection of the posterosuperior segments is challenging, and there are no data on the learning curve. The aim of this study was to evaluate the learning curve for laparoscopic resection of the posterosuperior segments.Methods: A cumulative sum (CUSUM) analysis of the difficulty score for resection was undertaken using patient data from four specialized centres. Risk-adjusted CUSUM analysis of duration of operation, blood los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…Whereas for minor laparoscopic liver resections the learning curve was 22 procedures [23], for major hepatectomy this was 45-55 procedure [24,25]. A recent study specifically assessing the learning curve for the posterosuperior segments concluded that the learning curve was estimated to be a total of 65 procedures for anatomical resections [26]. A factor that could shorten the learning curve is the use of specific training.…”
Section: Multivariable Regression Analysismentioning
confidence: 99%
“…Whereas for minor laparoscopic liver resections the learning curve was 22 procedures [23], for major hepatectomy this was 45-55 procedure [24,25]. A recent study specifically assessing the learning curve for the posterosuperior segments concluded that the learning curve was estimated to be a total of 65 procedures for anatomical resections [26]. A factor that could shorten the learning curve is the use of specific training.…”
Section: Multivariable Regression Analysismentioning
confidence: 99%
“…A recently published multicentre study evaluating the learning curve of LLRs in the postero-superior segments by CUSUM analysis of 464 patients, found that 40 and 65 procedures were needed to complete the learning curve for atypical and anatomical resections, respectively(93). This shows the complexity of these procedures.In a nationwide analysis from the Netherlands, reporting the data of 6951 procedures from 27 centres, the authors discovered that these 'technically major' liver resections are mostly limited to experienced surgeons, and are associated with greater operation time, blood loss, postoperative complications and postoperative hospital stay than resections in the antero-lateral segments (94).Several retrospective studies, a propensity score matched analysis and a meta-analysis, have shown, that in selected patients, LPSLR in the postero-superior segments provides similar or better perioperative outcomes when compared to open surgery(95)(96)(97)(98).…”
mentioning
confidence: 99%
“…Scientific literature has so far targeted the need to demonstrate that the laparoscopic approach overall confers short term benefits over the open counterpart while maintaining an adequate standard of care in terms of oncological results (1)(2)(3)(4)(5). A large amount of literature has indeed been published during the last 15 years, comparing mixed series of laparoscopic and open liver resections or series selected by single or few items, from the technical (minor and major, type of resections, topography of lesions) (1,3,16) or the pathological point of view (HCC, colorectal liver metastases, intrahepatic cholangiocarcinoma) (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%